Presepsin as a predictor of critical colonization in CLI hemodialysis patients. Issue 1 (4th February 2016) - Shiota, Jun; Ohura, Norihiko; Higashikawa, Shingo; Yamato, Tsunee; Kasahara, Hitoshi; Itatani, Keiichi; Tagawa, Hitoshi
ABSTRACT: Infection during critical limb ischemia (CLI) is a challenging issue. Plasma presepsin is a novel biomarker for infection, which is related to bacterial phagocytosis by macrophages. The purpose of this study was to investigate the validity of presepsin as an indicator and predictor for early detection of infectious CLI. A retrospective observational study was conducted among 20 CLI patients (Rutherford 5 and 6) on hemodialysis (HD). Twenty CLI patients on HD (mean age 70.7 ± 5.6 years, male 85%) and 15 healthy patients on HD without CLI and infection (control group) were analyzed. All CLI patients received appropriate revascularization and plastic surgical treatment. CLI patients were classified into two groups: the healing group with complete epithelialization without discharge and the nonhealing group with infection signs. Plasma presepsin was measured and compared among the two groups and the control group using an automated immunoanalyzer, PATHFAST, based on a noncompetitive chemiluminescent enzyme immunoassay. The median plasma presepsin and its interquartile range were 1, 320 (1, 055–1, 465) pg/mL in the control group, 1, 320 (1, 050–1, 613) pg/mL in the healing group and 3, 193 (2, 519–3, 832) pg/mL in the nonhealing group. The plasma presepsin concentrations were significantly higher in the nonhealing group compared with the control group ( p < 0.001) and the healing group ( p < 0.01). A receiver operating characteristic curve analysis revealed that presepsin had highest accuracy (0.979) among various inflammatory markers, including C‐reactive protein and the white blood cell count. The diagnostic cutoff value of 2, 083 pg/mL was able to distinguish the nonhealing group and healing group with a sensitivity of 100% and a specificity of 88.9%. Our results suggest that plasma presepsin may be useful for predicting "critical colonization" and "infection" in nonhealing CLI in HD patients, therefore, the definitive cutoff value may be used for determinating the indication for reintervention and/or major limb amputation.